High-definition anti-glare nano AG film and preparation method thereof

By using technical means such as reinforced modified PE diaphragm substrate and nano Ag film layer in the AG film, the problems of gloss, haze instability and uneven coating distribution of the existing AG film are solved, and the preparation of high-definition anti-glare nano AG film is achieved, which improves the light transmittance and anti-glare performance of the diaphragm.

CN119620255AActive Publication Date: 2025-03-14湖南壹鑫科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510165274.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-14
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

The existing AG films have unstable gloss, haze and roughness during use. The spraying process leads to uneven distribution of coating particles, causing flash points and affecting the display effect.

Method used

The combination of reinforced modified PE diaphragm substrate, nano zinc oxide transition layer, nano Ag film layer, reactor microstructure layer and modified surface protective film layer is used to coat the film through magnetron sputtering technology to form a high-definition anti-glare nano AG film.

Benefits of technology

It improves the hardness, electrical insulation and light transmission of the diaphragm, reduces the flash point phenomenon, improves the display effect, and enhances the anti-glare performance and acid corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119620255A_ABST
    Figure CN119620255A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of AG films, and particularly discloses a high-definition anti-glare nano AG film and a preparation method thereof. The high-definition anti-dazzle nanometer AG membrane comprises a membrane base material, a reaction synthesis microstructure layer and a first surface protection membrane layer, and the reaction synthesis microstructure layer and the first surface protection membrane layer are sequentially arranged on the surface of the membrane base material in a stacked mode. The preparation method of the high-definition anti-dazzle nanometer AG membrane comprises the steps that the membrane base material is smeared with an ultraviolet curing surface material to form a membrane layer; according to the method, the film layer is subjected to pressing and imprinting by utilizing an imprinting mold, and the imprinting microstructure layer of which the surface is randomly distributed with a plurality of pits, bulges or through holes is further obtained through illumination curing, so that the light can be changed from mirror reflection to diffuse reflection by utilizing the uneven surface structure of the imprinting microstructure layer while the glossiness and the transmittance are ensured; according to the invention, the interference on eyes is weakened, the anti-dazzle effect is achieved, the size uniformity and distribution uniformity of particles can be well controlled, the smoothness is good, the use hand feeling is improved, and the formation of flash points can be effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of AG films, and in particular to a high-definition anti-glare nano AG film and a preparation method thereof. Background Art

[0002] In recent years, with the development of the flat panel display industry, it has strongly promoted the production and research and development of optical functional films; AG film is a general term for a type of functional film, which is widely used by the public in the current market due to its good anti-fingerprint, oil pollution, high light transmittance and other characteristics; due to the instability of gloss, haze, roughness, etc. during use, and the spraying process easily leads to uneven distribution and inconsistent size of coating particles, causing flash points and affecting the display effect; touching the screen brings great inconvenience to use, therefore, the development of a hardened coating with high-definition anti-glare function is an urgent task. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a high-definition anti-glare nano AG film; another purpose of the present invention is to provide a method for preparing a high-definition anti-glare nano AG film.

[0004] Technical solution: A high-definition anti-glare nano AG film, which includes: a reinforced modified PE film substrate, a nano zinc oxide transition layer, a nano Ag film layer, a reaction accumulation microstructure layer, and a modified surface protective film; The preparation method of the reinforced modified PE film substrate is as follows: placing the PE film in a chlorine atmosphere, irradiating the film with a mercury lamp UV at 40°C for 8 hours to obtain a chlorinated PE film, taking out the chlorinated PE film, placing the chlorinated PE film in a 60% ethanol aqueous solution with a volume 10 times the weight of the chlorinated PE film, adding aluminum chloride with a weight 0.01 times the weight of the chlorinated PE film, ultrasonically dissolving, adding toluene with a weight 0.1 times the weight of the chlorinated PE film, ultrasonically reacting at an external temperature of 80°C for 4 hours, taking out and vacuum drying at 45°C to obtain the film; The preparation method of the reaction accumulation microstructure layer is as follows: under nitrogen protection, the PET film is placed in dichloromethane with a volume 5 times the weight of the PET film, and o-cresol with a mass 0.5 times the mass of the PET film and triphenylphosphine with a mass 1.2 times the mass of the PET film are added under ultrasound at 20°C, and the mixture is stirred to dissolve and clarify, and the system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass 0.9 times the mass of the PET film is added dropwise at the same temperature, and the system temperature is controlled not to exceed 15°C for reaction for 30 minutes after the addition is completed, and polyethylene glycol 6000 with a mass 2 times the mass of the PET film is slowly added, and the reaction is carried out under ultrasound for 2 hours, and the mixture is taken out and washed with ethanol, and dried at 50°C with air blowing. The preparation method of the modified surface protective film layer is as follows: a PET film is placed in neopentyl glycol with a volume 5 times the weight of the PET film, o-cresol with a mass 0.5 times the mass of the PET film and triphenylphosphine with a mass 1.2 times the mass of the PET film are added under ultrasound at 20°C, the solution is stirred to clarify, the system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass 0.9 times the mass of the PET film is added dropwise at the same temperature, ultrasonically reacted for 2 hours, taken out and washed with ethanol, and dried at 50°C by blowing air.

[0005] Preferably, the reinforced modified PE film substrate has a thickness ranging from 80 to 200 μm.

[0006] Preferably, the thickness of the nano zinc oxide transition layer is 20 nm.

[0007] Preferably, the thickness of the nano-Ag film layer is 50 nm.

[0008] Preferably, the thickness of the reaction-deposited microstructure layer PET film is in the range of 70 to 100 μm, the surface roughness Ra of the reaction-deposited microstructure layer is in the range of 0.01 to 0.05 μm, and the surface roughness Rsm is in the range of 2 to 16 μm.

[0009] Preferably, the surface protection film layer PET layer has a thickness ranging from 70 to 100 μm.

[0010] A method for preparing a high-definition anti-glare nano AG film comprises the following preparation steps: S1. Using a VTC-600-1HD single-target magnetron sputtering apparatus, a layer of nano zinc oxide was plated on the reinforced modified PE film substrate to obtain film material 1; S2, using a VTC-600-1HD single-target magnetron sputtering apparatus to coat a layer of silver film on the nano zinc oxide coated side of the film material 1 obtained in step 1), to obtain film material 2; S3, coating a layer of adhesive on one side of the silver film of the film material 2 obtained in step S2, and attaching the reaction-deposited microstructure layer thereon to obtain a film material 3; S4, coating a layer of adhesive on one side of the reaction-deposited microstructure layer of the film material 3 obtained in step S3, and then attaching a surface protection film layer thereto, so as to obtain the high-definition anti-glare low-flash point AG film.

[0011] Preferably, the adhesive used in step S3 and step S4 is a silicone resin, selected from any one of methyl MQ silicone resin and vinyl MQ silicone resin.

[0012] Beneficial effects: 1. The PE film substrate is reinforced and modified by chlorination and alkylation reaction, and the obtained substrate film is hard and has excellent electrical insulation; 2. Polyethylene glycol 6000 is deposited on the surface of PET material through photo-deposition reaction to form a micro-structured frosted layer, which is more uniform and has better light transmittance than embossing and other methods; 3. The PET material is modified by the photo-expansion reaction, and the obtained PET material has better impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic diagram of the chemical reaction of the reinforced and modified PE film substrate of the present invention.

[0014] Figure 2 It is a schematic diagram of the chemical reaction of the reaction stacking microstructure layer of the present invention.

[0015] Figure 3 It is a schematic diagram of the chemical reaction of the modified surface protection film layer of the present invention. DETAILED DESCRIPTION

[0016] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0017] Embodiment 1: Preparation of reinforced modified PE membrane substrate: A PE film with a thickness of 80 μm is placed in a chlorine atmosphere and irradiated with a mercury lamp UV at 40°C for 8 hours to obtain a chlorinated PE film, which is then taken out and placed in a 60% ethanol aqueous solution with a volume 10 times the weight of the chlorinated PE film, and aluminum trichloride with a weight 0.01 times the weight of the chlorinated PE film is added, and after ultrasonic dissolution, toluene with a weight 0.1 times the weight of the chlorinated PE film is added, and an external temperature of 80°C is ultrasonically reacted for 4 hours, and the film is taken out and dried in a vacuum oven at 45°C to obtain the film; Preparation of reactive stacked microstructure layers: Under nitrogen protection, a PET film with a thickness of 70 μm is placed in dichloromethane with a volume of 5 times the weight of the PET film, and o-cresol with a mass of 0.5 times the mass of the PET film and triphenylphosphine with a mass of 1.2 times the mass of the PET film are added under ultrasound at 20°C, stirred to dissolve and clarify, the system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass of 0.9 times the mass of the PET film is added dropwise at the same temperature. After the addition is completed, the system temperature is controlled not to exceed 15°C and reacted for 30 minutes, and polyethylene glycol 6000 with a mass of 2 times the mass of the PET film is slowly added, and the reaction is ultrasonically reacted for 2 hours, and the ethanol is taken out and washed, and the air is blown to dry at 50°C to obtain the obtained product; Preparation of modified surface protective film: A PET film with a thickness of 70 μm is placed in neopentyl glycol with a volume 5 times the weight of the PET film, and o-cresol with a mass 0.5 times the mass of the PET film and triphenylphosphine with a mass 1.2 times the mass of the PET film are added under ultrasound at 20°C. The mixture is stirred to dissolve and clarify. The system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass 0.9 times the mass of the PET film is added dropwise at the same temperature. The reaction is carried out by ultrasound for 2 hours, and the mixture is taken out, washed with ethanol, and dried at 50°C with air blowing.

[0018] The specific preparation process is: 1) using a VTC-600-1HD single target magnetron sputtering apparatus to deposit a 20 nm thick nano zinc oxide layer on the reinforced modified PE film substrate to obtain a film material 1; 2) using a VTC-600-1HD single-target magnetron sputtering apparatus to coat a layer of silver film with a thickness of 50 nm on the nano zinc oxide coating side of the film material 1 obtained in step 1), to obtain a film material 2; 3) coating a layer of methyl MQ silicone resin adhesive on one side of the silver film of the film material 2 obtained in step 2), and attaching the reaction-deposited microstructure layer to obtain the film material 3; 4) A layer of methyl MQ silicone resin adhesive is coated on one side of the reaction-deposited microstructure layer of the film material 3 obtained in step 3), and a surface protection film layer is attached to obtain the high-definition anti-glare low-flash point AG film.

[0019] Embodiment 2: Preparation of reinforced modified PE membrane substrate: A PE film with a thickness of 120 μm is placed in a chlorine atmosphere and irradiated with a mercury lamp UV at 40°C for 8 hours to obtain a chlorinated PE film, which is then taken out and placed in a 60% ethanol aqueous solution with a volume 10 times the weight of the chlorinated PE film, and aluminum trichloride with a weight 0.01 times the weight of the chlorinated PE film is added, and after ultrasonic dissolution, toluene with a weight 0.1 times the weight of the chlorinated PE film is added, and an external temperature of 80°C is ultrasonically reacted for 4 hours, and the film is taken out and dried in a vacuum oven at 45°C to obtain the film; Preparation of reactive stacked microstructure layers: Under nitrogen protection, a PET film with a thickness of 80 μm is placed in dichloromethane with a volume of 5 times the weight of the PET film, and o-cresol with a mass of 0.5 times the mass of the PET film and triphenylphosphine with a mass of 1.2 times the mass of the PET film are added under ultrasound at 20°C, stirred to dissolve and clarify, the system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass of 0.9 times the mass of the PET film is added dropwise at the same temperature. After the addition is completed, the system temperature is controlled not to exceed 15°C and reacted for 30 minutes, polyethylene glycol 6000 with a mass of 2 times the mass of the PET film is slowly added, and the reaction is ultrasonically reacted for 2 hours, and the ethanol is taken out and washed, and the air is blown to dry at 50°C to obtain the obtained product; Preparation of modified surface protective film: Place a PET film with a thickness of 80 μm in neopentyl glycol with a volume 5 times the weight of the PET film, add o-cresol with a mass 0.5 times the mass of the PET film and triphenylphosphine with a mass 1.2 times the mass of the PET film under ultrasound at 20°C, stir to dissolve and clarify, cool the system to 0±5°C, add diisopropyl azodicarboxylate with a mass 0.9 times the mass of the PET film at the same temperature, react with ultrasound for 2 hours, take out and wash with ethanol, and dry at 50°C with air blowing.

[0020] The specific preparation process is: 1) using a VTC-600-1HD single target magnetron sputtering apparatus to deposit a 20 nm thick nano zinc oxide layer on the reinforced modified PE film substrate to obtain a film material 1; 2) using a VTC-600-1HD single-target magnetron sputtering apparatus to coat a layer of silver film with a thickness of 50 nm on the nano zinc oxide coating side of the film material 1 obtained in step 1), to obtain a film material 2; 3) coating a layer of vinyl MQ silicone resin adhesive on one side of the silver film of the film material 2 obtained in step 2), and attaching the reaction-deposited microstructure layer to obtain the film material 3; 4) A layer of vinyl MQ silicone resin adhesive is coated on one side of the reaction-deposited microstructure layer of the film material 3 obtained in step 3), and a surface protection film layer is attached to obtain the high-definition anti-glare low-flash point AG film.

[0021] Embodiment three: Preparation of reinforced modified PE membrane substrate: A PE film with a thickness of 200 μm is placed in a chlorine atmosphere and irradiated with a mercury lamp UV at 40°C for 8 hours to obtain a chlorinated PE film, which is then taken out and placed in a 60% ethanol aqueous solution with a volume 10 times the weight of the chlorinated PE film, and aluminum chloride with a weight 0.01 times the weight of the chlorinated PE film is added, and after ultrasonic dissolution, toluene with a weight 0.1 times the weight of the chlorinated PE film is added, and an external temperature of 80°C is ultrasonically reacted for 4 hours, and the film is taken out and dried in a vacuum oven at 45°C to obtain the film; Preparation of reactive stacked microstructure layers: Under nitrogen protection, a PET film with a thickness of 100 μm is placed in dichloromethane with a volume of 5 times the weight of the PET film, and o-cresol with a mass of 0.5 times the mass of the PET film and triphenylphosphine with a mass of 1.2 times the mass of the PET film are added under ultrasound at 20°C, stirred to dissolve and clarify, the system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass of 0.9 times the mass of the PET film is added dropwise at the same temperature, and the system temperature is controlled not to exceed 15°C for reaction for 30 minutes after the addition is completed, and polyethylene glycol 6000 with a mass of 2 times the mass of the PET film is slowly added, and the reaction is ultrasonically reacted for 2 hours, and the mixture is taken out and washed with ethanol, and dried at 50°C with air blowing; Preparation of modified surface protective film: A PET film with a thickness of 100 μm is placed in neopentyl glycol with a volume 5 times the weight of the PET film, and o-cresol with a mass 0.5 times the mass of the PET film and triphenylphosphine with a mass 1.2 times the mass of the PET film are added under ultrasound at 20°C. The mixture is stirred to dissolve and clarify. The system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass 0.9 times the mass of the PET film is added dropwise at the same temperature. The mixture is ultrasonically reacted for 2 hours, and the mixture is taken out, washed with ethanol, and dried at 50°C with air blowing.

[0022] The specific preparation process is: 1) using a VTC-600-1HD single target magnetron sputtering apparatus to deposit a 20 nm thick nano zinc oxide layer on the reinforced modified PE film substrate to obtain a film material 1; 2) using a VTC-600-1HD single-target magnetron sputtering apparatus to coat a layer of silver film with a thickness of 50 nm on the nano zinc oxide coating side of the film material 1 obtained in step 1), to obtain a film material 2; 3) coating a layer of methyl MQ silicone resin adhesive on one side of the silver film of the film material 2 obtained in step 2), and attaching the reaction-deposited microstructure layer to obtain the film material 3; 4) A layer of methyl MQ silicone resin adhesive is coated on one side of the reaction-deposited microstructure layer of the film material 3 obtained in step 3), and a surface protection film layer is attached to obtain the high-definition anti-glare low-flash point AG film.

[0023] Comparative Example 1: The same as Example 1, except that the PE film substrate is not reinforced and modified.

[0024] Comparative Example 2: The same as the first embodiment, except that a conventional embossed PET film is used to replace the reaction-deposited microstructure layer.

[0025] Comparative Example 3: The same as the first embodiment, except that the PET protective film sheet is not modified.

[0026] The AG films obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the test results are shown in Table 1; Table 1 Test results of AG diaphragms of the embodiment and comparative example:

[0027] The results in Table 1 show that, from the data of Examples 1 to 3 and Comparative Example 1, reinforcing and modifying the PE film substrate can improve the film haze and total light transmittance; from the data of Examples 1 to 3 and Comparative Example 2, the use of a reactive stacking microstructure layer can improve the 60° gloss, haze and total light transmittance of the film; from the data of Examples 1 to 3 and Comparative Example 3, modifying the PET protective film film can effectively improve the corrosion resistance of the film. The high-definition anti-glare nano AG film prepared by the present invention has better product performance through the mutual cooperation of various components. By reinforcing and modifying the PE film substrate, modifying the surface protective film layer and preparing the reactive stacking microstructure layer, the film has a higher total light transmittance, better clarity, better anti-glare effect, and better acid corrosion resistance.

[0028] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high-definition anti-glare nano AG film, characterized in that: The high-definition anti-glare nano-AG film comprises: a reinforced modified PE film substrate, a nano zinc oxide transition layer, a nano Ag film layer, a reaction accumulation microstructure layer, and a modified surface protection film layer; The preparation method of the reinforced modified PE film substrate is as follows: placing the PE film in a chlorine atmosphere, irradiating the film with a mercury lamp UV at 40°C for 8 hours to obtain a chlorinated PE film, taking out the chlorinated PE film, placing the chlorinated PE film in a 60% ethanol aqueous solution with a volume 10 times the weight of the chlorinated PE film, adding aluminum chloride with a weight 0.01 times the weight of the chlorinated PE film, ultrasonically dissolving, adding toluene with a weight 0.1 times the weight of the chlorinated PE film, ultrasonically reacting at an external temperature of 80°C for 4 hours, taking out and vacuum drying at 45°C to obtain the film; The preparation method of the reaction accumulation microstructure layer is as follows: under nitrogen protection, the PET film is placed in dichloromethane with a volume 5 times the weight of the PET film, and o-cresol with a mass 0.5 times the mass of the PET film and triphenylphosphine with a mass 1.2 times the mass of the PET film are added under ultrasound at 20°C, and the mixture is stirred to dissolve and clarify, and the system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass 0.9 times the mass of the PET film is added dropwise at the same temperature, and the system temperature is controlled not to exceed 15°C for reaction for 30 minutes after the addition is completed, and polyethylene glycol 6000 with a mass 2 times the mass of the PET film is slowly added, and the reaction is carried out under ultrasound for 2 hours, and the mixture is taken out and washed with ethanol, and dried at 50°C with air blowing. The preparation method of the modified surface protective film layer is as follows: a PET film is placed in neopentyl glycol with a volume 5 times the weight of the PET film, o-cresol with a mass 0.5 times the mass of the PET film and triphenylphosphine with a mass 1.2 times the mass of the PET film are added under ultrasound at 20°C, the solution is stirred to clarify, the system is cooled to 0±5°C, and diisopropyl azodicarboxylate with a mass 0.9 times the mass of the PET film is added dropwise at the same temperature, ultrasonically reacted for 2 hours, taken out and washed with ethanol, and dried at 50°C by blowing air.

2. The high-definition anti-glare nano AG film according to claim 1, characterized in that: The reinforced modified PE film substrate has a thickness ranging from 80 to 200 μm.

3. The high-definition anti-glare nano AG film according to claim 1, characterized in that: The thickness of the nano zinc oxide transition layer is 20 nm.

4. The high-definition anti-glare nano AG film according to claim 1, characterized in that: The thickness of the nano-Ag film layer is 50nm.

5. The high-definition anti-glare nano AG film according to claim 1, characterized in that: The thickness of the reaction-deposited microstructure layer PET film is in the range of 70 to 100 μm, the surface roughness Ra of the reaction-deposited microstructure layer is in the range of 0.01 to 0.05 μm, and the surface roughness Rsm is in the range of 2 to 16 μm.

6. The high-definition anti-glare nano AG film according to claim 1, characterized in that: The surface protection film layer PET layer has a thickness ranging from 70 to 100 μm.

7. A method for preparing a high-definition anti-glare nano-AG film according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: S1. Using a VTC-600-1HD single-target magnetron sputtering apparatus, a layer of nano zinc oxide was plated on the reinforced modified PE film substrate to obtain film material 1; S2, using a VTC-600-1HD single-target magnetron sputtering apparatus to coat a layer of silver film on the nano zinc oxide coating side of the film material 1 obtained in step S1, to obtain film material 2; S3, coating a layer of adhesive on one side of the silver film of the film material 2 obtained in step S2, and attaching the reaction-deposited microstructure layer thereon to obtain a film material 3; S4, coating a layer of adhesive on one side of the reaction-deposited microstructure layer of the film material 3 obtained in step S3, and then attaching a surface protection film layer thereto, so as to obtain the high-definition anti-glare low-flash point AG film.

8. The method for preparing the high-definition anti-glare nano AG film according to claim 7, characterized in that: The adhesive applied in step S3 and step S4 is an organic silicone resin selected from any one of methyl MQ silicone resin and vinyl MQ silicone resin, and the adhesive coating thickness is 20 μm.

Citation Information

Patent Citations

  • Anti-glare protective film and preparation method thereof

    CN110531447A

  • Anti-dazzle optical film and production method thereof

    CN110673236A

  • Anti-glare antireflection film for display

    CN115508920A

  • Anti-reflection AG liquid crystal display panel

    CN116203752A

  • Optical film, manufacturing method thereof, display module and display device

    CN116931138A